Kinetic and Thermodynamics of Remazol Brilliant Blue R Adsorption - Bayrak, Yuksel; Uzgor, Resmiye (Asian Journal of Chemistry, 2013)
Orange peel, an agricultural solid waste abundantly available in Turkey, was utilized as a precursor for preparation of activated carbon via sulphuric acid chemical activation. The orange peel activated carbon (OPAC) is used for the removal of remazol brilliant blue R from aqueous solution. Research concerning the effects of pH, adsorbent dose, initial dye concentration and temperature are presented and discussed. Kinetic and thermodynamic parameters of adsorption were calculated.